STUDY ON THE SOCIOLOGICAL AND MOTIVATIONAL PROFILE OF FITNESS CENTER USERS IN RESITA MUNICIPALITY - CARABAS, Ionică; BICHESCU, Andrade Ionuț; DACICA, Liliana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: The insufficient level of physical activity among the population is a public health problem worldwide. According to the World Health Organization, over 27% of adults and approximately 80% of adolescents do not reach the minimum recommended levels of physical activity to maintain health. Technological development influences contemporary lifestyles, favoring inactivity. Regular physical activity is a viable alternative for maintaining optimal health, as well as for improving the quality of life. Group physical exercises are one of the more effective options for reducing stress and increasing the quality of life, compared to individual training. Fitness is an effective form of movement, helping us to be in shape both physically and mentally. Objective: To create a sociological and motivational profile of users of fitness centers in Reșița, Romania - demographic data, motivations, training preferences and social participation. Materials and methods: A 30-item cross-sectional questionnaire was administered to 87 clients of fitness centers (October 2024 - June 2025). Descriptive statistics and qualitative analyses were applied. Results: Respondents were mostly urban (90%) and male (68%), aged between 14 and 60 years and older (mostly 25-35 years). Over half had university degrees and full-time jobs. Most trained 3-5 times/week (71%) for 1-2 hours/session; For 71%, the gym was the only place where they practiced physical activity. Traditional resistance training (powerlifting/hypertrophy) predominated, with fewer choosing functional training or CrossFit. The main motivation was health and well-being ( 30%), followed by relaxation (22%); 9% of respondents cited medical reasons. Discussion: Users are young - middle-aged, educated and health-oriented - consistent with the known benefits of exercise (e.g., reducing anxiety, improving self-esteem), but with gaps in diet adherence ( 30%) and in proactively seeking professional guidance, despite high informational interest (78%). Personality preferences may influence choices regarding fitness modalities. Conclusions: Fitness centers in Reșița attract a socially active and health-conscious clientele; Expanding instructor-led education and inclusive offerings (e.g., beginner support, group activity formats) could broaden participation and maximize health impact, strengthening the evidence that physical exercise combined with social activities improves outcomes.